2019
DOI: 10.1016/j.neuroimage.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the spatiotemporal dynamics of self-generated, task-initiated thoughts with EEG and fMRI

Abstract: The temporal structure of self-generated cognition is a key attribute to the formation of a meaningful stream of consciousness. When at rest, our mind wanders from thought to thought in distinct mental states. Despite the marked importance of ongoing mental processes, it is challenging to capture and relate these states to specific cognitive contents. In this work, we employed ultra-high field functional magnetic resonance imaging (fMRI) and high-density electroencephalography (EEG) to study the ongoing though… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
232
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 209 publications
(292 citation statements)
references
References 98 publications
40
232
1
Order By: Relevance
“…In contrast to microstate temporal dynamics, the topographic configurations of microstates are strikingly consistent across published reports (Michel and Koenig, 2018). For the present study, microstate clusters A through E matched canonical patterns found in the literature (Michel and Koenig, 2018), including those observed in studies using data-driven approaches to determine an optimal number of clusters (Bréchet et al, 2019;Custo et al, 2017). Together, these five clusters explained 85% of the variance among subject-level cluster centroids, and 63% of the topographic variance (on average) seen in participants' resting EEG recordings.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In contrast to microstate temporal dynamics, the topographic configurations of microstates are strikingly consistent across published reports (Michel and Koenig, 2018). For the present study, microstate clusters A through E matched canonical patterns found in the literature (Michel and Koenig, 2018), including those observed in studies using data-driven approaches to determine an optimal number of clusters (Bréchet et al, 2019;Custo et al, 2017). Together, these five clusters explained 85% of the variance among subject-level cluster centroids, and 63% of the topographic variance (on average) seen in participants' resting EEG recordings.…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive performance was also predictive of microstate temporal parameters. Microstate duration was positively associated with psychomotor alertness (i.e., faster reaction times) for configurations A and B, and positively associated with response compatibility (i.e., greater response interference) for configurations A, B, C, and E. In prior work, the neural generators of microstates A and B have been linked to the spontaneous activity of visual and auditory sensory networks, respectively (Bréchet et al, 2019;Britz et al, 2010;Custo et al, 2017). As such, our findings would appear to indicate that the speeded responding and detection of target stimuli is facilitated by individual differences in the tendency for sensory networks to predominate at rest.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations